Infantile and Maternal Choriocarcinoma: A Case Report and Review of Literature - Ziba Mosayebi; Amir hosein Movahedian; Iran Malekzadeh (Mashhad University of Medical Sciences, 2016)
Background: Choriocarcinoma is a rare highly malignant trophoblastic neoplasm. It can be preceded by any form of gestation including a complete or a partial mole, miscarriage and normal pregnancy. Simultaneous intraplacental choriocarcinoma involving both mother and infant is extremely rare. Hepatomegaly, anemia, elevated ßHCG is the diagnostic triad. Here we report a 6 weeks old Afghan girl infant with intraplacental choriocarcinoma presented by severe anemia and widespread multiple metastatic lesions in liver, lung and brain with an elevated level of ßHCG . According to rarity of the disease, rapid progression and the high mortality rate with delay in diagnosis and intervation , choriocarcinoma should be one of the differential diagnosis in severe infantile and maternal anemia without any antecedent reason. According to highly vascular and friable nature of tumor, biopsy can be dangerous for diagnosis. As choriocarcinoma secrets ßHCG, measurement of serum ßHCG is the most common method used to diagnose choriocarcinoma